Choice of the method of protection of the information processing on personal computer against the leakage through the spurious electromagnetic radiation - Юхмич, Ю. В. (Problems of Informatization and Control, 2007)
An analysis of threat to information leakage processing on personal computer through the spurious electromagnetic radiation is conducted. The formation of the spurious electromagnetic radiation’s feald is investigated. Technical methods of prevention of information leakage through the spurious electromagnetic radiation is considered. The solution to the problems of prevention of information leakage through the spurious electromagnetic radiation is proved on a basis of an analysis of technical facilities and actions of protection of information